2021
DOI: 10.1177/08850666211070740
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Effect of COVID-19 Pandemic on Physical Well-Being and Mental Health of ICU Healthcare Workers in Turkey: A Single-Centre Cross-Sectional Later-Phase Study

Abstract: Background This study aimed to evaluate the effect of COVID-19 pandemic on physical well-being and mental health of ICU healthcare workers (HCWs). Methods A total of 51 ICU HCWs working at a tertiary care hospital were included in this cross-sectional study conducted before (January 2019-January 2020) and during (January 2021-April 2021) COVID-19 pandemic. Data on sociodemographic and work-related characteristics, COVID 19 history and current mental health issues via Hospital Anxiety-Depression Scale (HADS), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…Major factors associated with increased suicidality include higher rates of depression ( 27 , 32 , 33 , 36 , 37 , 39 , 40 , 55 ); anxiety ( 19 , 27 , 32 , 36 39 , 52 , 55 ); post-traumatic stress disorder ( 32 , 42 ); pre-pandemic lifetime mental disorders ( 24 ) or previous lifetime suicide attempt; insomnia severity; nightmare frequency; poorer subjective health ( 32 , 33 , 36 , 47 , 60 ); and burnout ( 32 ). In addition, other personal factors predisposing to suicidal thoughts include being female ( 58 ); having friends or family members infected with COVID-19 ( 24 , 32 , 56 ); living alone; having poor physical health ( 32 ); being single ( 27 , 39 ), divorced, legally separated, or widowed ( 24 ); higher alcohol consumption ( 32 , 34 ); psychotropic drug use ( 34 , 42 ); and change in vitamin D levels ( 45 ). Younger age is considered a risk factor for some participants ( 32 , 35 ), a protective factor for others ( 39 ), and shows no clear age pattern for the rest ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Major factors associated with increased suicidality include higher rates of depression ( 27 , 32 , 33 , 36 , 37 , 39 , 40 , 55 ); anxiety ( 19 , 27 , 32 , 36 39 , 52 , 55 ); post-traumatic stress disorder ( 32 , 42 ); pre-pandemic lifetime mental disorders ( 24 ) or previous lifetime suicide attempt; insomnia severity; nightmare frequency; poorer subjective health ( 32 , 33 , 36 , 47 , 60 ); and burnout ( 32 ). In addition, other personal factors predisposing to suicidal thoughts include being female ( 58 ); having friends or family members infected with COVID-19 ( 24 , 32 , 56 ); living alone; having poor physical health ( 32 ); being single ( 27 , 39 ), divorced, legally separated, or widowed ( 24 ); higher alcohol consumption ( 32 , 34 ); psychotropic drug use ( 34 , 42 ); and change in vitamin D levels ( 45 ). Younger age is considered a risk factor for some participants ( 32 , 35 ), a protective factor for others ( 39 ), and shows no clear age pattern for the rest ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare professionals reported physical and psychological ill-being during COVID-19. 5 , 6 “Ill-being” refers to physical and psychological health levels. 7 The increased level of ill-being refers to high anxiety, depression, fatigue, and sleepiness levels.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported poor and reduced SQ, as measured by the PSQI, with poor SQ prevalence ranging from 48.4% 69 to 96.1%. 70 Both, front line HCWs and non-front line HCW reported poor SQ and/or had moderate-severe stress. 71 In Saudi Arabia poor SQ levels were highest among front-line HCWs (emergency departments, intensive care units and wards).…”
Section: Resultsmentioning
confidence: 99%